Proton pump inhibitors in liver cirrhosis: a review of benefits and harms - Zhu, Jia; Yu, Haonan; Mancuso, Andrea; Qi, Xingshun (AME Medical Journal, 2017)
Proton pump inhibitors (PPIs) are acid suppressants, which can effectively control gastric acid secretion through inhibiting the H+/K+ ATPase of parietal cells. In recent years, PPIs are extensively prescribed in patients with liver cirrhosis. The impact of PPIs in such patients is controversial. Helicobacter pylori eradication and reduction of endoscopic treatment related complications are the potential benefits of PPIs in liver cirrhosis. By contrast, bone fracture, clostridium difficile infection (CDI), spontaneous bacterial peritonitis (SBP), and hepatic encephalopathy (HE) are the potential harms of PPIs in liver cirrhosis. Further, prospective studies are required to refine the special indications and contra-indications for PPIs in cirrhotic patients.